Real Options Models of the Firm, Capacity Overhang, and the Cross Section of Stock Returns - ARETZ, KEVIN; POPE, PETER F. (Journal of Finance, 2018)
ABSTRACT We use a stochastic frontier model to obtain a stock‐level estimate of the difference between a firm's installed production capacity and its optimal capacity. We show that this “capacity overhang” estimate relates significantly negatively to the cross section of stock returns, even when controlling for popular pricing factors. The negative relation persists among small and large stocks, stocks with more or less reversible investments, and in good and bad economic states. Capacity overhang helps explain momentum and profitability anomalies, but not value and investment anomalies. Our evidence supports real options models of the firm featuring valuable divestment options.